2008
DOI: 10.4103/0253-7613.40487
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Morus alba L. (mulberry) leaves on anxiety in mice

Abstract: Objective:The aim of the present work is to evaluate the anxiolytic effect of a methanolic extract of Morus alba L. leaves in mice.Materials and Methods:The hole-board test, elevated plus-maze paradigm, open field test, and light/dark paradigm were used to assess the anxiolytic activity of the methanolic extract of M. alba L. Morus alba extract (50, 100, and 200 mg/kg, i.p.) and diazepam (1 mg/kg, i.p.) were administered 30 min before the tests.Results:The results showed that the methanolic extract of M. alba … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(36 citation statements)
references
References 13 publications
(15 reference statements)
2
34
0
Order By: Relevance
“…Anxiolytic drugs reduce the natural aversion to light and increase the time spent in light area and number of transition from one compartment to other showed anxiolytic potential of compound. [16] In the present study, we found that “ 6g ” treatment significantly increased the time spent in lit compartment as well as number of transitions. Some studies have reported that an anxiolytic drug increased the transitions between the two compartments.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Anxiolytic drugs reduce the natural aversion to light and increase the time spent in light area and number of transition from one compartment to other showed anxiolytic potential of compound. [16] In the present study, we found that “ 6g ” treatment significantly increased the time spent in lit compartment as well as number of transitions. Some studies have reported that an anxiolytic drug increased the transitions between the two compartments.…”
Section: Discussionsupporting
confidence: 58%
“…In the EPM test increase number of entries and time spent into the open arms arm the most obvious index/reliable indicators of decreased anxiety or indicating the anxiolytic-like activity of a compound, while anxiogenic substances have the opposite effect. [121316] In our study, treatment with “ 6g ” produced anxiolytic-like effects in the EPM test at higher dose, as evidenced by increased percentages of both open arm entries and time spent in open arms. [12] In addition, diazepam used as reference anxiolytic also showed the potential anxiolytic effects in EPM.…”
Section: Discussionmentioning
confidence: 69%
“…We reviewed the available literature on diazepam for the three major rodent ARDEB assays: EPM, OF and LD. This review identified 172 articles Kawale, and Nade 2008;Yamada et al 2000;Yao et al 2010;Yasumatsu et al 1994;Zanoli et al 2002;L.-M. Zhang et al 2014;Zheng et al 2009). Calculation of an average Hedges' g (Cumming 2012) for 386 experiments revealed that diazepam had a very large effect on ARDEB, with a -1.26 g [95CI -1.36, -1.17] reduction compared with untreated control animals ( Figure 3, Table 2).…”
Section: Diazepam Produces a Moderate Reduction In Defense Behaviorsmentioning
confidence: 99%
“…1 Anxiety affects one-eighth of the population worldwide and has debilitating effects on the quality of life of many people. 2 Anxiety disorders can be identified by early diagnosis and effective treatment includes psychotherapy and use of drugs like benzodiazepines. [3][4] Conventional drug therapy have a narrow margin of safety between the anxiolytic effect and unwanted side effects, thus prompting researchers to evaluate new compounds specially plant based drugs having less undesirable effects.…”
Section: Introductionmentioning
confidence: 99%